2013
DOI: 10.1007/s10286-013-0191-0
|View full text |Cite
|
Sign up to set email alerts
|

Sympathetic withdrawal is associated with hypotension after hepatic reperfusion

Abstract: Objective Post-reperfusion syndrome (PRS), severe hypotension after graft reperfusion during liver transplantation, is an adverse clinical event associated with poorer patient outcomes. The purpose of this study was to determine whether alterations in autonomic control in liver transplant recipients prior to graft reperfusion are associated with the subsequent development of PRS. Methods Heart rate variability (HRV), systolic arterial blood pressure (SBP) variability, and baroreflex sensitivity of 218 liver tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 38 publications
3
18
0
Order By: Relevance
“…The loss of integrity of the vasoconstrictive response during graft reperfusion is also believed to be, at least partially, responsible for the development PRS[85,86]. …”
Section: Pre-transplant Risk Factors For Post-lt Prs-induced Akimentioning
confidence: 99%
See 1 more Smart Citation
“…The loss of integrity of the vasoconstrictive response during graft reperfusion is also believed to be, at least partially, responsible for the development PRS[85,86]. …”
Section: Pre-transplant Risk Factors For Post-lt Prs-induced Akimentioning
confidence: 99%
“…Garutti Martinez et al[85] reported a lower increase in vascular muscle tone reflected by an increased systemic vascular resistance index in patients experiencing PRS, suggesting a reduced vascular adaptability in these patients. A significant reduction in sympathetic tone has also been reported in patients who developed PRS[86]. Although altered cardiovascular autonomic control may not clarify the reason for the occurrence of graft reperfusion-related hypotension during LT, the assessment of autonomic indices may be helpful in predicting PRS occurrence and may help anaesthesiologist management in preventive treatment with vasoconstrictors before any substantial decrease in MAP in the first minutes after reperfusion.…”
Section: Pre-transplant Risk Factors For Post-lt Prs-induced Akimentioning
confidence: 99%
“…Its release to peripheral blood can be triggered by hypovolemia, hypotension, increase osmolarity, increased angiotensin II, etc [16]. Although it remains elusive as to how IR triggers the release of AVP, we believe this is most likely due to the transient hypotension caused by decreased venous blood return to the heart after the total portal pedicle occlusion, as well as reperfusion-induced hypotension [17]. Besides, other mechanisms may operate in this setting.…”
Section: Discussionmentioning
confidence: 99%
“…As for the graft preservative solution, histidine tryptophan ketoglutarate solutions were used in all patients. The anesthetic management, patient care, and hemodynamic data recruitment for LT surgery were performed according to the standard institutional protocol of Asan Medical Center, which was previously described in detail . Briefly, anesthesia was induced with thiopental sodium, fentanyl, and vecuronium.…”
Section: Methodsmentioning
confidence: 99%
“…The anesthetic management, patient care, and hemodynamic data recruitment for LT surgery were performed according to the standard institutional protocol of Asan Medical Center, which was previously described in detail. (9)(10)(11)(12)(13) Briefly, anesthesia was induced with thiopental sodium, fentanyl, and vecuronium. After endotracheal intubation, anesthesia was maintained with isoflurane or sevoflurane in a 50% air/oxygen mixture and continuous infusion of fentanyl and vecuronium.…”
Section: Surgical Technique and Anesthetic Managementmentioning
confidence: 99%